Quantitative Analysis of the Molecular Dynamics of P3HT:PCBM Bulk Heterojunction - Guilbert,AAY; Zbiri,M; Dunbar,ADF; Nelson,J (Journal of Physical Chemistry B, 2017)
The optoelectronic properties of blends of conjugated polymers and small molecules are likely to be affected by the molecular dynamics of the active layer components. We study the dynamics of regioregular poly(3-hexylthiophene) (P3HT):phenyl-C61-butyric acid methyl ester (PCBM) blends using molecular dynamics (MD) simulation on time scales up to 50 ns and in a temperature range of 250–360 K. First, we compare the MD results with quasi-elastic neutron-scattering (QENS) measurements. Experiment and simulation give evidence of the vitrification of P3HT upon blending and the plasticization of PCBM by P3HT. Second, we reconstruct the QENS signal based on the independent simulations of the three phases constituting the complex microstructure of such blends. Finally, we found that P3HT chains tend to wrap around PCBM molecules in the amorphous mixture of P3HT and PCBM; this molecular interaction between P3HT and PCBM is likely to be responsible for the observed frustration of P3HT, the plasticization of PCBM, and the partial miscibility of P3HT and PCBM.